Temperature induced biological alterations in the major carp, Rohu (Labeo rohita): assessing potential effects of climate change on aquaculture production - Mridul, Md. Monirul Islam; Zeehad, Md. Shariar Kabir; Aziz, Dania; Salin, Krishna R.; Hurwood, David A.; Rahi, Md. Lifat (Elsevier B.V., 2024)
Temperature plays a profound role in organismal growth, immunity, survival, and the entire biological systems of any aquatic species. Suboptimal temperature changes modify different biological traits of fish that adversely affect their life cycle and aquaculture productivity. The freshwater Indian major carp, Rohu (Labeo rohita), is one of the most important aquaculture species across the Indian Sub-continent, with the optimum temperature range of 28 °C to 32 °C. This study tested the effects of five different temperature levels (28 °C, 30 °C, 32 °C, 33 °C and 34 °C) on selected physiological and biochemical traits, and also on the expression of five targeted genes of L. rohita. Experimental temperatures significantly affected growth performance (mean body weight) (p < 0.05), with the highest growth and survival observed at 30 °C. The lowest level of growth and survival were obtained at 34 °C, possibly due to thermal stress, despite the highest O2 consumption rate and total blood cell counts found at this temperature. A significantly lower growth (P < 0.05) was observed at 28 °C (control) compared to 30 °C. The five target genes including growth hormone (GH) and insulin like growth factor I (IGF-I) as growth regulatory genes, glycerol-3-phosphatase (G-3-P) and Gherlin (as metabolic genes), and heat shock protein 70 (HSP70 as thermal stress response gene), showed variable expression levels with varying temperatures. The growth genes showed the highest expression at 28 °C and 30 °C, whereas the stress response gene showed the highest expression at 34 °C. Results of this study indicate that Rohu can perform well up to 32 °C without any adverse effects, with optimal production performance occurring between 28 °C and 30 °C. This further implies that appropriate measures must be in place to maintain optimum temperature in the aquaculture farms such as physically manipulating the production system to control temperature or through development of temperate tolerant strains in order to avoid potential negative consequences of climate change.